Valuing Assessment in Science Education: Pedagogy, Curriculum, Policy
VIII, 376 p. 34 illus.
Keywords: Assessment is a fundamental issue in research in science education, in curriculum development and implementation in science education as well as in science teaching and learning. This book takes a broad and deep view of research involving assessment in science education, across contexts and cultures (from whole countries to individual classrooms) and across forms and purposes (from assessment in the service of student learning to policy implications of system wide assessment). It examines the relationships between assessment, measurement and evaluation; explores assessment philosophies and practices in relation to curriculum and scientific literacy/learning; and details the relationships between assessment and science education policy. The third in a series, Valuing Assessment in Science Education has chapters from a range of international scholars from across the globe and staff from Monash University, King’s College London and University of Waikato. The two previousbooks in the series examined research relevant to the re-emergence of values in science education and teaching across the spectrum of science education as well as across cultural contexts through the professional knowledge of science teaching. This third book now moves to examine different aspects of generating understanding about what science is learnt, how it is learnt, and how it is valued. Valuing Assessment in Science Education will appeal to all those with some engagement with and/or use of research in science education, including research students, academics, curriculum development agencies, assessment authorities, and policy makers. It will also be of interest to all classroom science teachers who seek to keep abreast of the latest research and development and thinking in their area of professional concern.